Análise geoambiental da bacia hidrográfica do rio Apeú, nordeste paraense: subsídios ao planejamento ambiental - VALE, Jones Remo Barbosa (Universidade Federal do Pará, 2018)
The hydrographic basin of the Apeú river is located in the northeastern region of Pará, more precisely in the metropolitan mesoregion of Belém, it covers the municipalities of Castanhal, Santa Izabel do Pará and Inhangapí. The Apeú river basin presents itself as an important area for observation of the processes of landscape transformation, because this unit, during the last thirty years, underwent significant transformations, imposed by the dynamics of land use. This basin presents rural and urban characteristics, in this area there are socials and environmental problems, resulting from the absence or deficiency of public services. The main factors that contribute to the degradation of the basin are: the waterproofing of the soil, resulting from the urban expansion; lack of erosion control; removal of land cover for land use purposes; contamination and silting of the water courses. Given this context, this dissertation has the objective to provide subsidies to the environmental planning of this hydrographic basin. The methodology adopted in this research was developed by Rodriguez (1994) and Rodriguez et al. (1995), adapted to environmental planning by Leal (1995), this methodology contains the following steps: Inventory, Diagnosis and Proposals. The research was based on data and information about the physical environment, the dynamics of land use and vegetation cover, environmental legislation, social and economic information. The obtained results demonstrate that the landscape of the Apeú river basin has undergone a progressive process of transformation, due to the anthropic interference, resulting in different social and environmental problems, unaccompanied by effective policies of environmental planning and territorial ordening. The proposals presented aim to subsidize the environmental planning of the basin that should be a joint and organic initiative of the three municipalities that cover it.